2014
DOI: 10.1109/tns.2014.2298254
|View full text |Cite
|
Sign up to set email alerts
|

Proton Damage Comparison of an e2v Technologies n-channel and p-channel CCD204

Abstract: Abstract-Comparisons have been made of the relative degradation of charge transfer efficiency in n-channel and p-channel CCDs subjected to proton irradiation. The comparison described in this paper was made using e2v technologies plc. CCD204 devices fabricated using the same mask set. The device performance was compared over a range of temperatures using the same experimental arrangement and technique to provide a like-for-like comparison. The parallel transfer using the p-channel CCD was then optimised using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…It is based on the same architecture used in the CCD203, previously flown on board the Solar Dynamics Observatory launched in 2010 18 , but with the inclusion of a charge injection structure. Both p-channel 7,19 and n-channel 20 variants have been produced.…”
Section: Ccd204mentioning
confidence: 99%
See 3 more Smart Citations
“…It is based on the same architecture used in the CCD203, previously flown on board the Solar Dynamics Observatory launched in 2010 18 , but with the inclusion of a charge injection structure. Both p-channel 7,19 and n-channel 20 variants have been produced.…”
Section: Ccd204mentioning
confidence: 99%
“…The increased tolerance to displacement damage of a p-channel CCD was first demonstrated in 1997 2 and since then a number of other studies have demonstrated an improved hardness to radiation induced charge transfer inefficiency (CTI) when compared to n-channel CCDs [3][4][5][6][7] . The improvement has been linked to the number and type of defects formed within the buried channel, 3 and how these defects impact charge transfer, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of these defects increases after irradiation and an additional trap is generated with an energy of around 0.42 eV below the conduction band which is attributed to the phosphorous vacancy (E-centre). It was first demonstrated that a p-channel CCD could offer increased tolerance to displacement damage in 1997 3 , the improved tolerance has since been demonstrated in a number of other studies comparing p-channel and n-channel performance [4][5][6][7][8] The dopant used in p-channel is boron; boron has not been shown to have the same impact on CTE as the phosphorous dopant used in n-channel devices. Therefore, immediately there is less concentration of impurities from which stable defects can be formed that could impact charge transfer.…”
Section: Introductionmentioning
confidence: 99%